Problems in recordings for listening evaluation of the quality of violins - SASIN, Andrzej; KARUŻAS, Antoni; ŁĘTOWSKI, Tomasz (Archives of Acoustics, 1981)
This paper considers the possibility of performing a comparative evaluation of violin sound quality, based on sound recordings. The investigations dealt with the effect of the microphone techniques – mono, stereo AB and stereo XY– and the acoustics of the room, on the usefulness of the recordings made in given conditions for the evaluation of the sound quality of violins. The paper presents the investigation results and a comparison of these with the results of the "live" sound quality assessment performed by expert violinists.